Exclusion and extremism: a psychological perspective - Pfundmair, Michaela; Hales, Andrew H.; Williams, Kipling D. (Cambridge University Press, 2024)
The question of how people develop extreme, radical or even terrorist ideas and behaviors is one which is attracting more and more scientific attention. There are many factors that contribute to such extremist attitudes. This book focuses on one specific contributor which has received only little attention in the past: social exclusion. Recent research shows that being kept apart from others, physically or emotionally, is a powerful event in people's lives. The chapters provide an overview of the existing body of research for the first time and explore the exclusion-extremism link in depth by gathering together a seminal collection of essays, written by leading social psychologists. Timely, novel, and highly instructive, this volume delivers an expert understanding of psychological underpinnings of such behavior and offer inspiration for future research.